EFFECT OF NON-GENETIC FACTORS ON REPRODUCTIVE PERFORMANCE OF MURRAH BUFFALOES (Indian Journal of Animal Production and Management, 2013)
Data on 297 Murrah buffaloes maintained at Government Livestock Farm, Mamnoor, Warangal district of Andhra Pradesh, during 1969-2004 were utilized to study the effect of certain non-genetic factors on reproductive performance. The Least squares means for age at first calving, calving interval, dry period, gestation period and service period were 1548.41 ± 17.16 days, 397.64 ± 2.83 days, 146.36 ± 2.37 days, 303.82 ± 0.66 and 95.03 ± 2.79 days respectively. Season of birth had a non-significant influence on all the reproductive traits studied while period of birth significantly influenced age at first calving, calving interval and service period but not on dry period and gestation period.
Keywords: Andhra Pradesh; Murrah buffaloes; Reproductive performance